Antecedents of stream services purchase decision - Anggraini, Sinta Putri; Kusmantini, Titik; Salleh, Fauzilah (Universitas Ahmad Dahlan, 2023)
Purpose-Consumer decisions in choosing and buying a product are influenced by various internal and external factors. These factors can encourage or even reduce consumers’ intention to buy a desired product. This study chose brand image, brand image, and electronic word-of-mouth factors as determinants of consumer decisions to buy a product. Design/Methodology/Approach-This study chose consumers or users of Netflix streaming services in Yogyakarta as the respondents. The respondents used in this study were 130 respondents. The data obtained were processed using SPSS statistical tools to test the validity, reliability, and hypotheses. Findings-This study proves that brand image, brand trust, and electronic word-of-mouth have a positive influence on consumers’ purchase decisions. With these results, it can be seen that to encourage consumers to make purchases, there needs to be a positive image of the products offered, thus affecting consumer confidence in buying these products. These three aspects have been achieved, and consumers will influence other consumers to make purchases: in other words, electronic word-of-mouth affects purchasing decisions. Research limitations/implications- Consumer purchasing decisions in this study are influenced by brand image, brand trust, and electronic word-of-mouth. These three factors have been shown to have positive influences. That is, to encourage consumers to make product purchases, the image of the product and the trust of consumers must be maintained so that consumers remain encouraged to make purchases. When the image and trust are well maintained, consumers do not hesitate to influence other consumers to buy the product, so that electronic word-of-mouth can be achieved. Originality/value-This study discusses consumer behavior in terms of purchasing decisions regarding Netflix streaming services in Yogyakarta. Similar studies have been conducted using different variables and objects.